Das Ende eines internationalen Kaufmannshauses: Die "Haushaltsbücher" des Kaufmannsbankiers Stefan I. Loitz aus Tiegenhof bei Danzig, 1577-1580 - Markus A. Denzel (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– Using two household account books, this article analyses the family and staff, travel, consumption and flamboyance of the merchant-aristocratic household of the Loitz family in the 1570s. In 1572, the merchant-bankers Loitz, who had been highly successful in international trade and finance from Szczecin, Gdansk and Lüneburg for decades, had to overcome a drastic illiquidity crisis. Afterwards, they largely maintained the standard of living of a wealthy merchant or lower nobility, so that the decline of entrepreneurial activity did not lead to a fall in social standing for the entire family. The article also provides in-depth insights into the economic history of the Polish-Prussian region, characterized by agrarian farming, the grain and salt trades, and the persistence of the aristocracy.
Keywords: N23; N73; N83; 330; trade history; Loitz merchant family; Baltic Sea region; business history; manorial economy